Continuous diisobutylene manufacturing: Conceptual process design and plantwide control. (2nd February 2017) - Thakur, Shudodhan Singh; Ojasvi,; Kumar, Vivek; Kaistha, Nitin
Highlights: Simultaneous design encompassing flowsheet synthesis, optimization and plantwide control demonstrated for diisobutylene (DIB) manufacturing. Processes use tert -butyl alcohol (TBA) moderator, generated in-situ and recycled-to-extinction, for DIB yield enhancement. Two novel flowsheets, FS1 (brand new) and FS2, using a decanter for water recovery and recycle developed. FS1 and FS2 shown to achieve both high reactor conversion and DIB yield, unlike extant literature flowsheet, FS0. FS1 found to be superior to FS2 in terms of capital cost, energy efficiency and fresh water consumption. Demonstration of innovative control loops for yield and conversion regulation for "green" process operation. Abstract: The complete process design cycle encompassing flowsheet synthesis, design and controllability evaluation is studied for continuous DIB manufacturing. The residue curve map tool is applied to synthesize two new flowsheets, FS1 and FS2, exploiting pressure swing distillation. A unique feature of these is the use of a decanter for recovery and recycle of water, which allows maintaining the reactor tert -butyl alcohol content at the desired level for suppressing the side reaction. Unlike the literature flowsheet (FS0), this innovation makes it possible to achieve both high conversion and high yield for an economically superior design. Between FS1 and FS2, FS1 is found to be superior with significantly lower capital and energy costs as well as lower fresh water consumption. A "smart" control strategy for holding the single-pass reactor conversion and the overall process yield towards economic process operation is also developed. Rigorous dynamic simulations demonstrate the controllability of FS1 and FS2.